Fair Value Determination: A Conceptual Framework - Sara Aliabadi; Hong Chen; Alireza Dorestani (Journal of Accounting, Business and Management (JABM), 2011)
Financial crisis, failure of high profile corporations, new regulations and rules, expansion in globalization, and increasing fraudulent financial reporting have recently resulted in the rise of several accounting issues relevant to the capital market. Both the Financial Accounting Standard Board (FASB) and the International Accounting Standard Board (IASB) have been trying to promote fair value accounting to increase the information relevance of financial reports (Barth et al., 2007; Fiechter, 2010; Barlev and Haddad, 2003). However, critics of fair value accounting blame the flexibility and subjectivity of fair value accounting for many economics problems and financial crises. It is generally believed that fair value accounting produces more relevant financial information, but in some cases the fair value determination is subjective and is prone to management discretion and earnings manipulation. Our study shows that the literature in fair value determination is weak and universities generally do not offer any stand alone fair value related courses or programs. We believe that no conceptual framework for fair value determination has been developed, so in this paper we provide a theoretical framework for fair value determination and invite researchers to focus more in this very important area of specialization in fair value accounting. We also believe that traditional financial statements are only a partial process of accounting past and current financial position, and competitive position statement (CPS) is also a partial process of accounting for current and future financial position; therefore, we argue that the intersection of these two processes reflects the true current position unless the semantics for meaningful competitive interaction in a field is misread for an entitys decision making and implementation processes.